2020
DOI: 10.1097/md.0000000000022674
|View full text |Cite
|
Sign up to set email alerts
|

Local infiltration vs epidural analgesia for postoperative pain control after total knee or hip arthroplasty

Abstract: Background: Inconsistent results have been obtained regarding postoperative pain control using local infiltration and epidural analgesia for patients after total knee or hip arthroplasty (TKA and THA). We therefore conducted a meta-analysis of randomized controlled trials (RCTs) to assess the efficacy and safety of local infiltration vs epidural analgesia for TKA and THA. Methods: Electronic searches were conducted on PubMed, EmBase, and the Cochrane library to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…A recent meta-analysis showed that local anesthetic infiltration is superior to epidural analgesia for postoperative pain control after TKA. 23 Perhaps the doses and techniques used for periarticular LIA were likely inconsistent between the different operating surgeons in our study. Another systemic review and meta-analysis investigated and did not support adding iPACK block to ACB in the presence of periarticular LIA due to lack of any additional benefit.…”
Section: Discussionmentioning
confidence: 93%
“…A recent meta-analysis showed that local anesthetic infiltration is superior to epidural analgesia for postoperative pain control after TKA. 23 Perhaps the doses and techniques used for periarticular LIA were likely inconsistent between the different operating surgeons in our study. Another systemic review and meta-analysis investigated and did not support adding iPACK block to ACB in the presence of periarticular LIA due to lack of any additional benefit.…”
Section: Discussionmentioning
confidence: 93%
“… 37 Also in line with previous studies, we showed a mutually indistinguishable effect of LIA and FSNB 24 hours after surgery, 38 which was superior to the effects of post-op epidural opioids and intrathecal analgesics. 39 , 40 Since the systemic toxicity of LIA can affect up to 11% of patients, the post-op monitoring of LIA patients cannot be ignored. 41 A similar observation was made by Tian et al; their retrospective TKA study showed that the short-term analgesic effect of LIA was similar to that of nerve block and reduced the need for opiate supplementation, and that LIA and nerve block had similar complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have compared the efficacy of LAI against other postoperative analgesic strategies. LAI is associated with superior analgesic effect than epidural analgesia 33 with lower incidence of nausea and vomiting and a wider range of articular motion. 95 In the case of FNB, there was a similar effect in pain control compared to LAI.…”
Section: Regional Analgesia For Tkamentioning
confidence: 99%
“… 31 However, neuroaxial analgesia was associated with higher incidence of hypotension, urinary retention, nausea and vomiting. 31 On the other hand, researchers found that local infiltration provides better analgesia management than either subarachnoid 32 or epidural analgesia 33 for TKA. In favor of reducing opioid use, epidural analgesia provides superior pain control than intravenous opioids.…”
Section: Regional Analgesia For Tkamentioning
confidence: 99%